2019
DOI: 10.7717/peerj.7355
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation and symmetry of the inner-ear labyrinth in a population of wild turkeys: implications for paleontological reconstructions

Abstract: The cochlea and semicircular canals (SCCs) of the inner ear are vital neurosensory devices. There are associations between the anatomy of these sensorineural structures, their function, and the function of related biological systems, for example, hearing ability, gaze stabilization, locomotor agility, and posture. The endosseous labyrinth is frequently used as a proxy to infer the performance of the hearing and vestibular systems, locomotor abilities, and ecology of extinct species. Such fossil inferences are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…Moreover, the relationship between the length of the cochlear duct and the basisphenoid has also been shown to correlate with hearing frequencies in modern archosaurs (Walsh et al ., 2009), thus providing a way to calculate mean and high frequencies of non‐avian dinosaurs. A recent study using extant turkeys demonstrated that a shape analysis of a single endosseous labyrinth can be used to represent an entire population (Cerio and Witmer, 2019); we therefore suggest that the hearing frequencies calculated in this study can be used as proxies for high and average hearing frequencies for V. mongoliensis . By measuring and logarithmically transforming the ratio between the cochlear duct length and the total length of the basisphenoid, a mean hearing range (2,368 Hz) and high‐frequency hearing limit (3,965 Hz) was calculated for IGM 100/976—a range that is comparable to birds such as the common raven ( Corvus corax ) and the African penguin ( Spheniscus demersus ) (Walsh et al ., 2009).…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, the relationship between the length of the cochlear duct and the basisphenoid has also been shown to correlate with hearing frequencies in modern archosaurs (Walsh et al ., 2009), thus providing a way to calculate mean and high frequencies of non‐avian dinosaurs. A recent study using extant turkeys demonstrated that a shape analysis of a single endosseous labyrinth can be used to represent an entire population (Cerio and Witmer, 2019); we therefore suggest that the hearing frequencies calculated in this study can be used as proxies for high and average hearing frequencies for V. mongoliensis . By measuring and logarithmically transforming the ratio between the cochlear duct length and the total length of the basisphenoid, a mean hearing range (2,368 Hz) and high‐frequency hearing limit (3,965 Hz) was calculated for IGM 100/976—a range that is comparable to birds such as the common raven ( Corvus corax ) and the African penguin ( Spheniscus demersus ) (Walsh et al ., 2009).…”
Section: Discussionmentioning
confidence: 68%
“…We segmented right labyrinths and retained them for the numerical analyses (see below); if these were not preserved, then the left labyrinth was segmented and mirrored. A recent study found no significant bilateral variation in the inner ears of wild turkeys (37), justifying this procedure. We also show that left-right asymmetry is minimal in extant crocodylians (SI Appendix, Figs.…”
Section: Methodsmentioning
confidence: 90%
“…It is possible that the variation in canal shape in Champsosaurus is due to a sedentary lifestyle, but a much larger sample size is needed to determine if the variation in Champsosaurus canal morphology is atypical. A study describing the semicircular canals of several individuals at varying ontogenetic stages within each species of Champsosaurus would also describe whether the variation in morphology between CMN 8920 and CMN 8919 is typical for the genus, or is due to interspecific or ontogenetic variation between 104 .…”
Section: Resultsmentioning
confidence: 99%